2016
DOI: 10.1111/nep.12692
|View full text |Cite
|
Sign up to set email alerts
|

Time to recovery from haemodialysis : location, intensity and beyond

Abstract: Home-based HD and higher residual urine volumes are significantly associated with shorter RT. This home advantage for RT may be sustained by preserving residual renal function (in early stages) and increasing HD intensity (in later stages) of dialysis therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 17 publications
1
17
2
Order By: Relevance
“…This finding is in disagreement with that of previous studies that have demonstrated a significant association between a longer recovery time and the female sex [4][5]9].…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…This finding is in disagreement with that of previous studies that have demonstrated a significant association between a longer recovery time and the female sex [4][5]9].…”
Section: Discussioncontrasting
confidence: 57%
“…Little is known about the determinants of recovery time [5][6][7]. Recently, we have demonstrated that recovery time is significantly associated with post-dialysis fatigue and that the severity of post-dialysis fatigue was negatively and weakly associated with the ultrafiltration rate (UFR) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Modalities such as frequent HD and hemodiafiltration (HDF) can achieve a high adequacy and more fluid removal while maintaining hemodynamic stability, which may lead to better DRT (5,(12)(13)(14). The Frequent Hemodialysis Network (FHN) trial and observational studies have demonstrated frequent HD leads to lower DRT compared to thrice weekly HD (5,12).…”
Section: Discussionmentioning
confidence: 99%
“…DRT has been shown to be a reliable and valid marker of health-related quality of life (HRQOL) (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Prior studies indicated that >65% of prevalent HD patients report DRT ≥2 hours (9,15).…”
Section: Introductionmentioning
confidence: 99%
“…The patient-reported experience on both LDNHD and SDHD has been positive in terms of physical, psychological and lifestyle aspects [68]. There is also an associated faster recovery time with home haemodialysis [69]. Once again, it is fair to say once again that the jury is still with regard to whether these treatments truly impact on quality of life.…”
Section: Quality-of-life Measures and Carer Burdenmentioning
confidence: 99%